1994
DOI: 10.1002/gcc.2870100104
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplastic syndrome transforming to acute promyelocytic‐like leukemia with trisomy and rearrangement of chromosome II

Abstract: Variants of the t(15;17)(q22;q12-q21) chromosomal rearrangement associated with acute promyelocytic leukemia (APL) have been previously described and they frequently involve either chromosome 15 and/or 17. Previously we reported a rare variant t(11;17). We now describe two patients with myelodysplastic syndrome (MDS) that transformed to APL-like leukemia. Both had trisomy 11 at the diagnosis of APL-like leukemia. Following treatment for APL, patient 1 reverted to MDS and showed a normal karyotype. When leukemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…In fact, the majority of JT donor chromosome breakpoints reported in hematologic malignancies have been located within constitutive heterochromatic regions, in particular proximal 1q. [2][3][4][5]7,8,[10][11][12][13][15][16][17] The recipient breakpoints are regularly reported to be cytogenetically telomeric. It is tempting to speculate that a general shortening of telomeric sequences would increase the susceptibility for such illegitimate recombinations, facilitating the origin of multiple rearrangements, ie, jumping translocations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the majority of JT donor chromosome breakpoints reported in hematologic malignancies have been located within constitutive heterochromatic regions, in particular proximal 1q. [2][3][4][5]7,8,[10][11][12][13][15][16][17] The recipient breakpoints are regularly reported to be cytogenetically telomeric. It is tempting to speculate that a general shortening of telomeric sequences would increase the susceptibility for such illegitimate recombinations, facilitating the origin of multiple rearrangements, ie, jumping translocations.…”
Section: Discussionmentioning
confidence: 99%
“…To date, JT have been reported in one solid tumor and in 18 various hematologic malignancies, mainly lymphoid disorders such as acute lymphoblastic leukemia (ALL) and non-Hodgkin lymphoma (NHL). [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] As acquired abnormalities, JT are unbalanced, involve non-random donor and recipient chromosome regions, and are associated with disease progression and a usually fatal outcome. In fact, 11 of 16 reported cases with clinical information died shortly after the appearance of JT; four of the five patients who achieved complete remission had had ALL or NHL with t(8;14)(q24;q32).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of both PML-RARa and PLZF-RARa fusions with the APL phenotype argues for a key role for RARa in the hybrid genes. In support of this is the observation that two cases of myelodysplastic syndrome transformed to APL with trisomy 11 without RARa rearrangements, failed to respond to ATRA (20). However, since the role ofPML and PLZF in leukemic cell proliferation and differentiation remains largely unknown, it is also possible that PML and PLZF have an equivalent function when rearranged with the RARa gene.…”
Section: Resultsmentioning
confidence: 93%
“…The immunophenotype of their leukemia cells was CD34 + (both patients) and HLA-DR + (data only available for one patient), and they possessed wild type RARα genes without the PML-RARα chimera gene (both patients). Moreover, both patients failed to respond to ATRA treatment (9). On the other hand, Wolach et al reported a case of therapy-related APL developing through a phase of therapyrelated MDS, which responded to ATRA treatment.…”
Section: Discussionmentioning
confidence: 99%